2022
DOI: 10.1002/jmv.27814
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell responses to SARS‐CoV‐2 Omicron spike epitopes with mutations after the third booster dose of an inactivated vaccine

Abstract: The rapidly spreading severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) Omicron variant contains more than 30 mutations that mediate escape from antibody responses elicited by prior infection or current vaccines. Fortunately, T‐cell responses are highly conserved in most individuals, but the impacts of mutations are not clear. Here, we showed that the T‐cell responses of individuals who underwent booster vaccination with CoronaVac were largely protective against the SARS‐CoV‐2 Omicron spike protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
(90 reference statements)
4
12
0
Order By: Relevance
“…Our results were similar to previous research, which indicated that boosting ChAdOx1 after completing 2 shots of CoronaVac elicited a higher number of RBD-specific IgG than those without the boosting [5]. Several studies found that three doses of inactivated or mRNA vaccine resulted in a more significant immunogenic response than two doses [13, 14].…”
Section: Discussionsupporting
confidence: 91%
“…Our results were similar to previous research, which indicated that boosting ChAdOx1 after completing 2 shots of CoronaVac elicited a higher number of RBD-specific IgG than those without the boosting [5]. Several studies found that three doses of inactivated or mRNA vaccine resulted in a more significant immunogenic response than two doses [13, 14].…”
Section: Discussionsupporting
confidence: 91%
“… 81 Similarly, several studies predicted that the memory mediated by T cells in individuals with prior infection (WT or previous VOCs) and vaccination (with EMA‐approved vaccines) has preserved reactivity to the Omicron variant, especially their reactivity is enhanced by booster vaccination. 82 , 83 , 84 , 85 , 86 , 87 Surprisingly, the percentage of participants with prior infection and/or vaccination had a >50% reduction in T‐cell response to Omicron spike was higher than Delta (21.2% vs. 9.7%), potentially due to escape of HLA‐I restricted epitopes. 83 ” Therefore, it is important to understand protection against these VOCs may be hidden in cross‐reactive SARS‐CoV‐2‐specific T‐cell mediated immunity.…”
Section: Introductionmentioning
confidence: 96%
“…It is yet to discover what level of immunity is required to prevent hospitalization and death, but real-world data suggest that vaccination is successful in preventing these even in the presence of transmissible and virulent variants of concern (VOCs). [ 56 , 76 ] In the future, repeated boosting might be necessary to maintain long-term immunological memory of SARS-CoV-2 and VOCs, especially for immunocompromised populations such as PLWH. Therefore, there is a need to increase the surveillance of the virus so that effective measures can be taken promptly.…”
Section: Discussionmentioning
confidence: 99%